Simulasi Monte Carlo dalam Estimasi Distribusi Pendapatan dan Evaluasi Kelayakan Finansial UMKM Teh Poci - Bintang, Bintang; Alya, Nazwa; Nisrina, Hernita Zaida; Ramadhan, Risky Setiawan; Fachrezy, Galih (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze income distribution and evaluate the financial feasibility of Teh Poci MSMEs using a Monte Carlo simulation approach. The data consist of daily revenue over the last 30 days, which were processed to construct a probabilistic monthly income distribution through 10,000 simulation iterations. The results indicate that the average monthly revenue is approximately IDR 46.82 million, with a near-normal distribution and relatively low variability. The probability of achieving the target revenue of IDR 45 million exceeds 90%, while the Value at Risk (VaR) remains within an acceptable threshold. Sensitivity analysis reveals that small changes in daily average revenue significantly affect monthly projections. Overall, the Monte Carlo approach provides a comprehensive risk assessment framework and demonstrates that the Teh Poci MSME is financially feasible under normal operating conditions.